Differentiation Between Phyllodes Tumor and Fibroadenoma Using Real-Time Elastography - Adamietz, B. R.; Kahmann, L.; Fasching, P. A.; Schulz-Wendtland, R.; Uder, M.; Beckmann, M. W.; Meier-Meitinger, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2011)
Purpose: Phyllodes tumors (PT) are a rare entity accounting for less than 1 % of all breast lesions. They have a malignancy rate of 25 – 30 %. Differentiation from benign fibroadenomas is difficult using ultrasound, mammogram and MRI. The elastic characteristics of both tumors were examined using real-time elastography (RTE) to find specific patterns that make differentiation possible. Materials and Methods: From February 2007 to May 2009, a total of 620 women were examined by RTE. Histological diagnosis was achieved using core needle biopsy. 123 of the lesions were fibroadenomas, 8 were phyllodes tumors. All patients underwent mammography and ultrasound followed by RTE. Sonography was performed by Acuson Antares, Premium Edition® (Siemens, Erlangen, Germany) with a 7 and 10 MHz transducer. Results: All phyllodes tumors had a similar elastic pattern with an elastic center and inelastic outer limits, referred to as the “ring sign”. It was found in 5 % of all fibroadenomas. Conclusion: RTE provides a specific elastic pattern, which is sufficient for differentiating between a fibroadenoma and a phyllodes tumor. Therefore, the detection of the most suspicious lesion in women with the coexistence of multiple fibroadenomas and phyllodes tumors seems easier.
Keywords: fibroadenoma; phyllodes tumor; elastography; breast